2021
DOI: 10.1002/app.50556
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and study of stable fluorine‐free superhydrophobicity of cotton fibers

Abstract: This paper proposes a method of directly modifying the surface of cotton fiber to achieve super‐hydrophobic properties. The process was directly utilized the long‐chain alkyl siloxane and the nano‐SiO2 modified cotton cloth, which was simple to operate, low in cost and environmentally friendly. This study discussed the influence of solvent ratio, reactant content and ammonia content on hydrophobicity. The solvent ratio had the greatest influence, and the maximum water contact angle (CA) changes were70° ± 1°. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…The DTG curves (differential form of TGA) are shown in Figure D. The weight loss peak of CF (Figure D­(a)) at 346 °C can be attributed to the decomposition of the cellulose chain of the cotton fabric. ,, The weight loss peak of CF-PDA (Figure D­(b)) appeared at 325 and 442 °C, respectively. Besides, the weight loss was lower than that of CF.…”
Section: Resultsmentioning
confidence: 99%
“…The DTG curves (differential form of TGA) are shown in Figure D. The weight loss peak of CF (Figure D­(a)) at 346 °C can be attributed to the decomposition of the cellulose chain of the cotton fabric. ,, The weight loss peak of CF-PDA (Figure D­(b)) appeared at 325 and 442 °C, respectively. Besides, the weight loss was lower than that of CF.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the textured and hydrophobic nature of the waxes found on lotus leaves are what made it superhydrophobic 2 . Since the illumination of the self‐cleaning effect of the lotus leaf, various endeavors have been undertaken to fabricate superhydrophobic surfaces with practical application in mind, such as self‐cleaning surfaces, 3–7 water repellent textiles, 8–14 and membranes/interfaces for oil/water separation 15–19 …”
Section: Introductionmentioning
confidence: 99%
“…Besides, the deposition of a colloidal dispersion of hydrophobic nanoparticles or mixtures of nanoparticles with hydrophobic molecules is a convenient method where fabrics of all types, be it cotton, polyester, lining, nylon, and so on, can be coated using dip coating or spray coating methods. A common nanoparticle of choice is SiO 2 , which is commercially available and can be also easily synthesized 10,14,25–27 . For example, Y.D.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations